Effect of Undaria Pinnatifida Aqueous Extracts on Phytopathogenic Fungi - Miracola, Antonella (2024)
Currently, the intensive use of synthetic pesticides is being replaced by sustainable and effective solutions to control phytopathogens. A promising alternative is the use of biostimulants which offer a potential replacement for traditional agrochemicals, reducing their application rates and increasing crop quality and yields. In particular, algae as biostimulants have demonstrated highly beneficial properties on plant growth, tolerance to biotic and abiotic stresses, and crop yields. In Argentina, the brown macroalga Undaria pinnatifida was accidentally introduced in 1992 onthe Patagonia coast (Puerto Madryn harbor) and then expanded both southward and northward, including the southeast Buenos Aires province coast. This work aimed to evaluate the effect of aqueous extracts of U. pinnatifida, enriched indifferent bioactive compounds, on the inhibition of two phytopathogenic fungi such as Fusarium solani and Botrytis cinerea. To this end, various methodologies were used to obtain differentially enriched U. pinnatifida extracts: T1,Room temperature extraction x 1 h; T2, 60 ºC x 1 h; and T3, 90 ºC x 15 min; and tested their antimicrobial activity in vitro against both pathogens. The results showed that the three aqueous extracts (T1, T2, and T3) decreased the length of F. solani hyphae in a dose-dependent manner. This effect remained until lower concentrations for T2 extract(1:1000), suggesting that T2 extract is mostly enriched in compounds capable of producing this effect. It has beenproposed that the decrease in hyphal length is related to possible interferences in cell wall synthesis. When all extracts were evaluated against B. cinerea, they increased the hyphal width compared to the control, at all higher concentrations, being this effect more pronounced with T2. The differences in hyphal morphology could be attributed to the relative concentrations of bioactive compounds present in each of the extracts, due to the different extraction temperatures used.Further studies on their identification should be carried out to optimize their potential use as antimicrobial compounds.Considering the high costs and negative aspects of pesticide applications, it is desirable to promote the use of natural compounds to minimize their use. We expect that the application of Undaria extracts with the highest antimicrobial activity, may constitute a beneficial alternative within a sustainable crop management program.